Male Infertility : Where is the Research Heading? A Bibliometric Perspective - Saddam Muhdi; Mofri Lindo; Muhamad Topan Firdaus (International Journal of Medicine and Health, 2025)
Male infertility is a growing concern in reproductive health, affecting millions worldwide. Despite its significant impact on couples' ability to conceive, it remains underexplored compared to female infertility. This study offers a comprehensive bibliometric analysis of male infertility research, identifying trends, key contributors, and emerging areas of focus. By analyzing publication patterns, leading journals, influential authors, and collaborative networks, we aim to provide a nuanced understanding of the current state and future directions of this research field. The insights gained are expected to guide future investigations, enhance collaborations, and inform policymakers and clinicians about this evolving area. A systematic literature search was conducted in Scopus and Web of Science databases to retrieve relevant publications on male infertility. ScientoPy was used and bibliometric indicators, such as publication output, citation analysis, author collaboration networks, and keyword co-occurrence analysis, were used to explore the intellectual structure and research trends in this domain. Visualization tools, including VOSviewer, were employed to present the findings. The analysis included 2726 publications spanning from 2014 to 2024. The results reveal the most productive authors, influential journals, and highly cited publications in the field. Key research themes, emerging topics, and the evolution of the research landscape are discussed. Collaborations among authors, institutions, and countries are also examined to identify the intellectual structure and global research networks. This analysis provides valuable insights into the current state of research on male infertility The findings highlight the critical areas of focus, influential studies, and collaborative patterns that have shaped the field. Implications for future research directions, evidence-based practice, and potential areas for interdisciplinary collaboration are discussed.